2003
DOI: 10.1002/jcb.10507
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and differentiation of osteoblasts and adipocytes in rat bone marrow stromal cell cultures: Effects of dexamethasone and calcitriol

Abstract: During bone loss, osteoblast population can be replaced by adipose tissue. This apparent reciprocal relationship between decreased bone density and increased fat formation can be explained by an imbalance in the production of bone-forming and fat-forming cells in the marrow cavity. Thus, osteoblast and adipocyte pathways seem more closely and inversely related. In the present study, we investigated the effects of dexamethasone (dex) and calcitriol [1,25(OH)(2)D(3)] on proliferation and differentiation of osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 60 publications
8
45
0
1
Order By: Relevance
“…FABP4, product of the aP2 gene, is regulated by dexamethasone in mouse 3T3L1 cells (Cook et al 1988) as well as in differentiating preadipocytes from rat bone marrow (Atmani et al 2003). This study verified FABP4 gene as a glucocorticoid-target gene but only in SC preadipocytes.…”
Section: Adipose-specific Genessupporting
confidence: 64%
“…FABP4, product of the aP2 gene, is regulated by dexamethasone in mouse 3T3L1 cells (Cook et al 1988) as well as in differentiating preadipocytes from rat bone marrow (Atmani et al 2003). This study verified FABP4 gene as a glucocorticoid-target gene but only in SC preadipocytes.…”
Section: Adipose-specific Genessupporting
confidence: 64%
“…This was detected with fetal as well as with adult cells. The combining action of the two hormones was described to strongly increase the adipocyte population and their differentiation but to decrease the osteoblastic cell population in a long-term rat bone marrow culture [55]. Osteoblastic cell proliferation and differentiation were increased by dexamethasone and inhibited by 1a,25-(OH) 2 D 3 .…”
Section: Discussionmentioning
confidence: 97%
“…Dexamethasone, however, was omitted as it was proven in rat bone marrow stromal cells that dexamethasone per se acts at multiple points in the differentiation process to stimulate osteoblastic maturation. [34][35][36] It has also been suggested that dexamethasone inhibits prostaglandin synthesis. 37 Since PGE 2 is a down-stream product of AA investigated in this study, it was important not to interfere with PGE 2 production.…”
Section: Osteogenic Supplemented Mediamentioning
confidence: 99%